2016
DOI: 10.1039/c6ra04528f
|View full text |Cite
|
Sign up to set email alerts
|

Abnormally high oscillator strengths of the graphene nanoribbons electronic spectrum: quantum chemistry calculations

Abstract: Armchair-edged narrow graphene nanoribbons (GNRs) are modelled by semi-empirical Hartree–Fock based quantum chemistry method ZINDO/S-CI. ​Abnormally high oscillator strengths of over 200 are found in long GNRs (length > 150 hexagonal carbon rings).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Different TD-DFT methods (TD-B3LYP, TD-PBE0, and TD-M06–2X) and basis sets (6-31G* and 6-31+G*) were employed to calculate the lowest-energy electronic transitions of both molecules in the chosen solvents (see Table S3 in Supporting Information). High oscillator strengths were found for these transitions ( f ≥ 1.2; see Table ) in agreement to the previous observations reported for compound 3b , other related phenylenevinylenes, and, in general, systems with large number of conjugated rings such as coumarins, porphyrins, phthalocyanines, and graphene nanoribbons, among others. , The combination of TD-M06–2X and 6-31+G* yielded the best match between calculated and experimental values. The higher percentage of HF-like exchange in M06-2X, compared to B3LYP and PBE0, reduces any possible underestimation in the calculation of the excited-state energies, in agreement with previous works. ,, According to the findings obtained with TD-M06-2X/6-31+G*, the lowest energy absorption band of compound 1 corresponds to two π–π* electronic transitions whose main components are HOMO–1 → LUMO and HOMO → LUMO electronic excitations (see Table ).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Different TD-DFT methods (TD-B3LYP, TD-PBE0, and TD-M06–2X) and basis sets (6-31G* and 6-31+G*) were employed to calculate the lowest-energy electronic transitions of both molecules in the chosen solvents (see Table S3 in Supporting Information). High oscillator strengths were found for these transitions ( f ≥ 1.2; see Table ) in agreement to the previous observations reported for compound 3b , other related phenylenevinylenes, and, in general, systems with large number of conjugated rings such as coumarins, porphyrins, phthalocyanines, and graphene nanoribbons, among others. , The combination of TD-M06–2X and 6-31+G* yielded the best match between calculated and experimental values. The higher percentage of HF-like exchange in M06-2X, compared to B3LYP and PBE0, reduces any possible underestimation in the calculation of the excited-state energies, in agreement with previous works. ,, According to the findings obtained with TD-M06-2X/6-31+G*, the lowest energy absorption band of compound 1 corresponds to two π–π* electronic transitions whose main components are HOMO–1 → LUMO and HOMO → LUMO electronic excitations (see Table ).…”
Section: Resultssupporting
confidence: 88%
“…High oscillator strengths were found for these transitions (f ≥ 1.2; see Table 2) in agreement to the previous observations reported for compound 3b, other related phenylenevinylenes and, in general, systems with large number of conjugated rings such as coumarins, porphyrins, phthalocyanines and graphene nanoribbons, among others. 17,[52][53][54][55][56][57] The combination of TD-M06-2X and 6-31+G* yielded the best match between calculated and experimental values. The higher percentage of HF-like exchange in M06-2X, compared to B3LYP and PBE0, reduces any possible underestimation in the calculation of the excited-state energies, in agreement with previous works.…”
Section: Resultsmentioning
confidence: 84%
“…The graphene nanoflakes are in between oligo-layered graphene sheet and higher carbon–carbon structures (i.e., graphite), , and their optical and transitional properties are of high interest of general physical chemistry for wider understanding of carbon structures. The morphology and physicochemical properties of graphene have been studied by spectroscopy, that is, UV–vis, infrared, Raman, , circular dichroism, and X-ray photoelectron spectroscopy, as well as theoretical calculations, focusing not only on electronic structure and closely related properties ,,,,,,, but also on morphology ,,,, and interactions. ,, Electronic properties of graphene not only remain in the center of attention of physical chemistry but also are essential for advanced material chemistry. For example, graphene properties are being studied in the context of development of novel sensors , and nanoelectronics . Recently, Zheng et al reported potential usefulness of the FUV photovoltaic detector with p-type graphene and aluminum nitride AlN .…”
Section: Introductionmentioning
confidence: 99%